TESTING THE CAUSAL RELATIONSHIP BETWEEN MONEY SUPPLY AND ECONOMIC GROWTH IN IRAQ USING (GRANGER TEST AND TODA YAMAMOTO TEST) (World Economics and Finance Bulletin, 2022)
This research aims to attempt to highlight the extent of the existence of a relationship between the money supply and economic growth in Iraq during the period (2003-2020). The standard study data include each of the three components of the money supply (M1,M2,M3) and real economic growth rates. Where the research is divided into three parts according to modern research methodologies. In the first part, we touched on the most important modern applied studies, and in the second part we dealt in detail the path of each of the components of the money supply and real economic growth in Iraq. As for the third part, we devoted it to a standard study on the relationship between the money supply and economic growth in Iraq, and the study found that there are A one-way causal relationship between the money supply in the narrow sense that causes GDPat pricesThe fixed and one-way causal relationship between the money supply in the broad sense and the gross domestic productat pricesPersistent and there is no causal relationship betweenShownIn the broadest sense, monetary and gross domestic productat pricesfixed Using the causality test presented byGranger using the Toda Yamamoto Extended TestThe results of the failure to achieve the monetary school's point of view showed that there is no long-term relationship between the money supply and economic growth.